Influence of physical activity on prevention and occurrence of spinal deformities in children during development - Lazić, Irena; Petronić Marković, Ivana; Sindjić Antunović, Sanja; Nikolić, Dejan; Aleksić, Tanja; Bukumirić, Dragica (Vojnosanitetski pregled, 2021)
Background/Aim. The published data indicate that the appearance of spinal deformities in children is significantly influenced by physical activity. The aim of our study was to examine the influence of physical activity on prevention and occurrence of spinal deformities in children. Methods. The study was conducted as observational, clinical study in the period from 2016 to 2018. Participants were children with spinal deformities, which were examined, for the first time, by physiatrists and pediatric surgeons. The sample included 100 children with spinal deformities, aged 7–17 years. The control group consisted of 100 children without spinal deformity, of similar age. The study instrument was a questionnaire based on a survey filled by children or parents/legal guardians. The questions were related to different parameters of the possible significance for the existence of spinal deformity and especially to the influence of physical activity. The collected data were processed using methods of descriptive and analytical statistics. Results. Scoliosis the most common deformity of the spinal column, represented in about 67% of children (p = 0.0006). Respondents from both groups did not differ significantly in terms of gender. Children in the group with spinal deformities were older (11.5 ± 3.1 years vs. 10.4 ± 3.1 years, p = 0.016), with increased body weight (43.9 ± 16.0 kg vs. 39.3 ± 16.6 kg, p = 0.046) and height (151.7 ± 17.2 cm vs. 145.8 ± 18.2 cm, p = 0.019), as well as with less physical activity (81.0% vs. 92.02%, p = 0.001). Over 80% of children were regularly engaged in physical activity, more often recreationally and on average 2.5–3 hours per week. Conclusion. Children in the spinal deformity group were significantly less involved in physical activity than the control group, but there was no significant difference in the frequency and duration of time spent in physical activities during the week. It is important for children to be involved in physical activities of a recreational nature, and according to our research, 3 hours during the week.